2020
DOI: 10.1002/essoar.10502892.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observational evidence for the role of Hall conductance in Alfvén wave reflection

Abstract: Electromagnetic energy carried by magnetohydrodynamic modes is an important mechanism in the energy transfer between the magnetosphere and the ionosphere. Alfvén waves are known to carry field-aligned currents and thus play an important role in the dynamics of the ionosphere-magnetosphere coupling. The role of Hall conductance in this interplay has been explored in magnetohydrodynamic models of the ionosphere but has hitherto not been observed in situ. We use 5 years of observations from the Swarm mission to s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, given a fuller understanding of precipitation‐induced energy injection, analyses of break‐points in plasma density spectra can give observational constraints on the distribution of high‐latitude E‐region conductance. This method can work in synergy with other methods of diagnosing ionospheric conductances, which could be based on ionospheric reflection coefficients (e.g., Ivarsen et al., 2020; Pakhotin et al., 2018), or on global FAC density maps ((Robinson et al., 2021), and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given a fuller understanding of precipitation‐induced energy injection, analyses of break‐points in plasma density spectra can give observational constraints on the distribution of high‐latitude E‐region conductance. This method can work in synergy with other methods of diagnosing ionospheric conductances, which could be based on ionospheric reflection coefficients (e.g., Ivarsen et al., 2020; Pakhotin et al., 2018), or on global FAC density maps ((Robinson et al., 2021), and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a large distance between the geographic and geomagnetic south poles (Jin & Xiong, 2020), causing the southern hemisphere polar region to exhibit a wider range of SZA values than in the northern hemisphere. Second, recent studies have found that the northern hemisphere is characterized by stronger field‐aligned currents that cannot be explained by differing SZA distribution (Ivarsen et al., 2020; Workayehu et al., 2020), as well as stronger energy input in the form of Poynting flux (Pakhotin et al., 2021). As we have shown, during local winter, SSI occurrence rates are dependent on auroral particle precipitation, and so the local winter hemispheric asymmetry in SSI occurrence rates should be seen in this context.…”
Section: Discussionmentioning
confidence: 99%